Economic thought according to Muhammad bin Makki al-Amili (d .: 786 AH) in companies, companies, and Islamic economic thought - Abdul Amir, Mazin Sabah (Al-Adab Journal, 2015)
English summary:Lies the importance of the subject he is trying to highlight the aspect of economic thought in the Arab-Islamic state, the Arabs have been known companies since the pre-Islamic era and excelled in the ill-trade which they have invested large amounts of money to the Arabs realized the importance of the company was their trade often based on the basis of the company between individuals, some of whom contributes his work and sometimes work and sometimes contributes individual contributes them with money and work, and the profits and losses are distributed to certain ratios agree among themselves. When Islam came to work on refining assets of these companies and their business and select economic.The company is a contract in the Islamic sense, which is a personal element and the joint agreement of the parties in the affirmative and acceptance mainly in the formation of companies, it is closer to the legal meaning because the company is not only satisfied and acceptance.